Dark blue-green: Cave-inhabiting cyanobacteria as a model for astrobiology - Jung, Patrick; Harion, Felix; Wu, Shujie; Nürnberg, Dennis J.; Bellamoli, Francesco; Guillen, Antonio; Leira, Manuel; Lakatos, Michael (Frontiers in Astronomy and Space Sciences, 2023)
Subterranean environments on Earth serve as an analog for the study of microbes on other planets which has become an active area of research. Although it might sound contradictory that photosynthetic cyanobacteria thrive in extreme low light environments, they are frequent inhabitants of caves on Earth. Throughout the phylum these cyanobacteria have developed unique adaptations that can not only be used for biotechnological processes but also have implications on astrobiology. Besides their adaptation strategies to accommodate for the low light conditions by producing specific pigments that allow photosynthesis in near-infrared radiation / far-red light, they can synthesize bioplastic compounds and calcium carbonate sheaths which represent valuable resources during human colonization of other planets or rock bodies. This article will highlight the potential benefits of cave-inhabiting cyanobacteria and will present a suitable bioreactor technique for the utilization of these special microbes during future space missions.